The Effect of Foot Massage and Lavender Aromatherapy on Rheumatoid Arthritis Pain Intensity in the Elderly in the Public Health Center Jembatan Kecil Bengkulu City - Heriyanto, Hendri; Awanis, Hasyyati; Mardiani (POLTEKKES KEMENKES PADANG, 2023)
In Indonesia, one of the highest health complaints experienced by the elderly is rheumatoid arthritis. In the province of Bengkulu in 2018 there were 13.2% or around 8,620 people of rheumatoid arthritis affecting the elderly. The purpose of this study was the fear of the influence of foot massage therapy and lavender aromatherapy on the intensity of rheumatoid arthritis pain in the elderly. This study used Pre-Experimental Designs in the form of one group pre-test and post-test design. This technique uses consecutive sampling of 30 people. Pain data collection used the Numeric Rating Scale (NRS) before and after intervention. Therapy carried out for 3 days with 15 minutes each for 2 weeks. Univariate analysis used Mean, Standard Deviation, Median, Minimum, Maximum and 95% CI. And bivariate analysis using paired t-test with 5%. Pain intensity in the elderly before being given foot massage therapy and lavender aromatherapy were 5.13 (moderate pain) and after being given foot massage therapy and lavender aromatherapy 3.03 (mild pain). The results of the paired t-test statistical test obtained ap value of 0.000 (p < 0.05). The results of the paired t-test statistical test obtained ap value of 0.000 (p < 0.05). There is an effect of foot massage therapy and lavender aromatherapy on the intensity of rheumatoid arthritis pain in the elderly. It is hoped that the staff can apply foot massage therapy and lavender aromatherapy as a safe and practical non-pharmacological method as an alternative in reducing pain intensity.